Energetics of the isomers: 3-and 4-hydroxycoumarin - Clara C S Sousa (2010)
This paper reports a combined thermochemical experimental and computational study of the two isomers 3- and 4-hydroxycoumarin. The standard (ir = 0.1 MPa) molar enthalpies of formation in the condensed state of the compounds were derived from the standard molar energies of combustion in oxygen at T= 298.15 K. measured by combustion calorimetry. Calvet microcalorimetry was used to derive the standard molar enthalpies of sublimation. By combining these values, the standard molar enthalpies of formation in the gaseous phase, at T= 298.15K, were derived (367.7 +/- 1.9) kJ mo1-1 for 3-hydroxycoumarin and (351.4 +/- 2.4) kl.mo1-1 for 4-hydroxycoumarin. The temperatures of fusion, Tfus, and fusion enthalpies, at T= T(fus), are also reported. Additionally, high-level density functional theory calculations using the B3LYP hybrid exchange-correlation energy functional with extended basis sets, as well as more sophisticated calculations using Doubly Hybrid Density Functional Theory (DHDFT) and more accurate correlated computational techniques of the MCCM suite have been performed for both compounds. The aromaticity of the hydroxycoumarins has been studied using Nucleus Independent Chemical Shifts (NICS) techniques and compared to that of non-substituted coumarin.